The determination of heavy metals in selected mangrove plants in estuarine environment - Norasyikin, Suhaili (Universiti Malaysia Sarawak, UNIMAS, 2008)
The aim of this study was to determine the heavy metals in the selected mangrove plants i.e. Avicennia sp. and Sonneratia sp. in the estuarine environment. The analysis of heavy metals was done in their roots, barks and leaves tissues and also sediment at the base of the mangrove plant analysed. The heavy metal studied were manganese (Mn), zinc (Zn), iron (Fe) and cadmium (Cd) and were analyzed using Atomic Absorption Spectroscopy (AAS). The findings of this study showed that Fe has highest concentration in all plant tissues followed by Mn, Zn and Cd. The mean concentrations of heavy metals in the plant tissues were according to descending order: Fe > Mn > Zn > Cd. Meanwhile, the mean concentrations of heavy metals were found in the sediment were according to descending order: Fe > Zn > Mn > Cd. Cd and Zn in the sediment in some study might be classified as heavily polluted.